2008
DOI: 10.1158/1535-7163.mct-08-0488
|View full text |Cite
|
Sign up to set email alerts
|

Salirasib (farnesyl thiosalicylic acid) for brain tumor treatment: a convection-enhanced drug delivery study in rats

Abstract: Our aim was to assess the ability of convection-enhanced drug delivery (CED), a novel approach of direct delivery of drugs into brain tissue and brain tumors, to treat brain tumors using salirasib (farsnesyl thiosalicylic acid). CED was achieved by continuous infusion of drugs via intracranial catheters, thus enabling convective distribution of high drug concentrations over large volumes while avoiding systemic toxicity. Several phase II/III CED-based trials are currently in progress but have yet to overcome t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…It has been reported that farnesyl thiosalicylic acid (FTS), a farnesyl-derived drug [42], could inhibit tumour growth by dislodging oncogenic Ras proteins from cell membranes by competitively binding to the Gal-1 farnesyl-binding site [18,43,44]. However, detailed structural information of the molecular basis for the acting mechanism in tumour growth inhibitory role of FTS is not well understood.…”
Section: Reduced K28t Hgal-1 Has No Farnesyl Binding Abilitymentioning
confidence: 99%
“…It has been reported that farnesyl thiosalicylic acid (FTS), a farnesyl-derived drug [42], could inhibit tumour growth by dislodging oncogenic Ras proteins from cell membranes by competitively binding to the Gal-1 farnesyl-binding site [18,43,44]. However, detailed structural information of the molecular basis for the acting mechanism in tumour growth inhibitory role of FTS is not well understood.…”
Section: Reduced K28t Hgal-1 Has No Farnesyl Binding Abilitymentioning
confidence: 99%
“…21 FTS also inhibits tumor growth, cell migration, and energy metabolism in numerous cancer cell lines and many types of cancer cells that exhibit high Ras GTP levels. 22, 23, 24, 25, 26 The most recent clinical trials showed that oral salirasib treatment of patients with pancreatic cancer increases survival rates (http://www.concordiapharma.com). …”
mentioning
confidence: 99%
“…22, 23, 24, 25, 26 An interesting additional outcome of FTS treatment in tumor cells is energy crisis. 27 Malignant cells, even under aerobic conditions, rely mostly on glycolysis for their energy supply.…”
mentioning
confidence: 99%
“…The current de facto clinical standard is gadolinium-based magnetic resonance imaging (MRI). Contrast surrogate agents, such as Gd-DTPA (Magnavist, Bayer) (7), can be co-infused with a drug to mimic the distribution of therapeutic agents delivered by CED (8,9). However, Gd-based contrast agents are not effective therapeutics on their own, and require micromolar quantities to resolve (1012).…”
Section: Introductionmentioning
confidence: 99%